Komunikasi Pemasaran Sampoerna Hijau Dalam Poster Untuk Memperluas Sektor Daya Beli Konsumen - Pranasa, Risyaf Kudus; Lazuardi, Ashar Banyu (Universitas Bumigora, 2024)
The main goal of marketing communications is to increase sales and build strong relationships with customers. This can be proven by the increasing number of new entrepreneurs emerging, especially entrepreneurs operating in the fieldmarketing on line. One of them is a product accountcigarette ieSampoerna Green. Sampoerna Green known as a manufacturerkretek type cigarettes which has long been known to the Indonesian people.This type of research uses a qualitative descriptive research approach. Qualitative research methods are research that aims to understand the phenomena experienced by research subjects, for example behavior, perceptions, motivations, actions and so on in a holistic manner. In practice, marketing strategies via Instagram accounts such as those carried out by the Sampoerna Hijau account have indeed mushroomed on social media, not only carried out by accounts with large numbers of followers, but also Instagram accounts with less than 100 thousand followers. carry out advertisements by using figures or artists who are considered capable of conveying their communication messages. Sampoerna Hijau is very aggressive in building branding to become Kretek Cigarettes which are described as having closeness between friends or companions. Sampoerna Hijau really understands how to build emotions in the audience or consum.